Pengaruh Interaksi Ibu Dan Anak Terhadap Perkembangan Bahasa Anak Usia Dini Usia 5-6 Tahun di TK Cerdas Ceria Desa Tapian Nauli - Elen Veralija Pasaribu; Ledyana Dwi Mei Situngkir; Mei Lastri E. F Butar Butar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of mother-child interaction on the language development of early childhood aged 5–6 years at TK Cerdas Ceria, Tapian Nauli Village. Language development in early childhood is an essential aspect that not only functions as a tool for communication but also influences cognitive, social, and emotional growth. Mother-child interaction, as a two-way communication involving attention, affection, and verbal stimulation, is believed to play a significant role in supporting the optimization of children’s language abilities. The research empl6oyed a quantitative approach with an ex post facto design. The population consisted of 13 children in group B at TK Cerdas Ceria, all of whom were included as the sample using a saturated sampling technique. Data were collected using questionnaires distributed to mothers and analyzed through simple linear regression with SPSS 27. The results of the data analysis show that there is an influence of mother-child interaction on the language development of early childhood aged 5-6 years at TK Cerdas Ceria, Tapian Nauli Village, as proven through the following data analysis: 1.Analysis Requirements Test: a. The test for a positive influence yielded an rxy value of 0.754. The calculated r-value was compared with the r-table value (α=0.05; CI=95%; n=13), which is 0.514, resulting in a calculated r-value > r-table value (0.754 > 0.514). Therefore, there is a positive relationship between variable X and variable Y. b. The significance test for the relationship yielded a t-calculated value of 3.810 > t-table value (α=0.05, dk=n-2=13) of 2.201. Thus, there is a significant relationship between variable X and variable Y. 2.Influence Test: a. The regression equation test is Ŷ = 41.033 + 0.135X. b. The Coefficient of Determination test (r²) shows a value of 56.9%. 3.Hypothesis Test: From the hypothesis test results, a calculated F-value > F-table value (14.516 > 4.75) was obtained, so the research hypothesis is accepted. It can be concluded that Ha is accepted and H0 is rejected.